Generational Change on the Tourism Labour Market - Bednarska, Marlena; Grobelna, Aleksandra (Studia Oeconomica Posnaniensia, 2017)
For the first time ever, the employees of three generations are working together, side by side in the same organisations. Although, all of them hold different work expectations, desires or working styles, it is said that particularly challenging is the youngest generation entering the labour market (Generation Y), whose work values may be significantly different than those that went before them. Therefore the purpose of the paper is to examine the effect of generational differences on the importance of work values in the tourism industry. To reach the objective of the study a survey was conducted with a group of 1,047 tourism employees. The research revealed that both job characteristics and employer location attractiveness contribute to the prediction of job satisfaction. The significance of these factors is partially moderated by generational differences. The youngest generation on the tourism labour market attribute more importance to social relations in the workplace and to the locational aspects of the employer.